Hypospadias: a review - Palacios-Rodríguez, Patricia M.; Romero, Juan J. Granados; Montalvo-Hernández, Jorge; Vázquez-González, Juan C.; Mendizabal-Velazquez, Alondra; González-Martínez, Itaty C.; Abundez-Pliego, Ana L.; Valderrama-Treviño, Alan I.; Barrera-Mera, Baltazar (International Journal of Research in Medical Sciences, 2023)
Hypospadias is a congenital malformation of the male external genitalia, which includes: anomalous location proximal to the urethral meatus, in any portion of the glans penis and perineum, hooded dorsal foreskin, and inverted penile curvature on the dorsal side of the foreskin. The etiology has been considered multifactorial, secondary to the interaction of environmental factors with specific genetic background. It represents the second most frequent congenital defect in male newborns. It has increasing prevalence rates of 0.25 new cases per 10,000 newborns per year. Risk factors that have been identified include infants small for gestational age with weight below the 10th percentile, head length and/or circumference, intrauterine growth restriction, and placental insufficiency. Regarding environmental risk factors, maternal exposure to pesticides has been linked. Prenatal diagnosis has been described, however proximal hypospadias is usually detected, making it difficult to diagnose distal hypospadias using this method. So usually the diagnosis is made after birth during the physical examination. To date, more than 300 surgical techniques are known for the correction of hypospadias. The treatment of distal hypospadias is currently performed in one time; the management of proximal hypospadias is controversial; one group favors the one-stage procedure, while other groups choose to perform the two-stage procedure.